3D model for Cancerous Inhibitor of Protein Phosphatase 2A armadillo domain unveils highly conserved protein–protein interaction characteristics. (7th December 2015) - Dahlström, Käthe M.; Salminen, Tiina A.
Abstract: Cancerous Inhibitor of Protein Phosphatase 2A (CIP2A) is a human oncoprotein, which exerts its cancer-promoting function through interaction with other proteins, for example Protein Phosphatase 2A (PP2A) and MYC. The lack of structural information for CIP2A significantly prevents the design of anti-cancer therapeutics targeting this protein. In an attempt to counteract this fact, we modeled the three-dimensional structure of the N-terminal domain (CIP2A-ArmRP), analyzed key areas and amino acids, and coupled the results to the existing literature. The model reliably shows a stable armadillo repeat fold with a positively charged groove. The fact that this conserved groove highly likely binds peptides is corroborated by the presence of a conserved polar ladder, which is essential for the proper peptide-binding mode of armadillo repeat proteins and, according to our results, several known CIP2A interaction partners appropriately possess an ArmRP-binding consensus motif. Moreover, we show that Arg229Gln, which has been linked to the development of cancer, causes a significant change in charge and surface properties of CIP2A-ArmRP. In conclusion, our results reveal that CIP2A-ArmRP shares the typical fold, protein-protein interaction site and interaction patterns with other natural armadillo proteins and that, presumably, several interaction partners bind into the central groove of the modeled CIP2A-ArmRP. By providing essential structural characteristics of CIP2A, the present study significantly increases our knowledge on how CIP2A interacts with other proteins in cancer progression and how to develop new therapeutics targeting CIP2A. Graphical abstract: Highlights: 3D structural model for the armadillo domain of CIP2A. Centrally located groove is involved in protein–protein interactions. A highly conserved polar ladder can mediate peptide binding. Cancer-causing Arg229Gln mutation disrupts surface charge distribution.